Investigation in the cannabigerol derivative VCE-003.2 as a disease-modifying agent in a mouse model of experimental synucleinopathy - Sonia Burgaz; Elisa Navarro; Santiago Rodríguez-Carreiro; Carmen Navarrete; Martin Garrido-Rodríguez; Isabel Lastres-Becker; Julia Chocarro; José L. Lanciego; Eduardo Muñoz; Javier Fernández-Ruiz (Behavioral and Brain Functions, 2024)
Abstract Background The cannabigerol derivative VCE-003.2, which has activity at the peroxisome proliferator-activated receptor-γ has afforded neuroprotection in experimental models of Parkinson’s disease (PD) based on mitochondrial dysfunction (6-hydroxydopamine-lesioned mice) and neuroinflammation (LPS-lesioned mice). Now, we aim to explore VCE-003.2 neuroprotective properties in a PD model that also involves protein dysregulation, other key event in PD pathogenesis. Methods To this end, an adeno-associated viral vector serotype 9 coding for a mutated form of the α-synuclein gene (AAV9-SynA53T) was unilaterally delivered in the substantia nigra pars compacta (SNpc) of mice. This model leads to motor impairment and progressive loss of tyrosine hydroxylase-labelled neurons in the SNpc. Results Oral administration of VCE-003.2 at 20 mg/kg for 14 days improved the performance of mice injected with AAV9-SynA53T in various motor tests, correlating with the preservation of tyrosine hydroxylase-labelled neurons in the SNpc. VCE-003.2 also reduced reactive microgliosis and astrogliosis in the SNpc. Furthermore, we conducted a transcriptomic analysis in the striatum of mice injected with AAV9-SynA53T and treated with either VCE-003.2 or vehicle, as well as control animals. This analysis aimed to identify gene families specifically altered by the pathology and/or VCE-003.2 treatment. Our data revealed pathology-induced changes in genes related to mitochondrial function, lysosomal cell pathways, immune responses, and lipid metabolism. In contrast, VCE-003.2 treatment predominantly affected the immune response through interferon signaling. Conclusion Our study broadens the neuroprotective potential of VCE-003.2, previously described against mitochondrial dysfunction, oxidative stress, glial reactivity and neuroinflammation in PD. We now demonstrate its efficacy against another key pathogenic event in PD as α-synuclein dysregulation. Furthermore, our investigation sheds light on the molecular mechanisms underlying VCE-003.2 revealing its role in regulating interferon signaling. These findings, together with a favorable ADMET profile, enhance the preclinical interest of VCE-003.2 towards its future clinical development in PD.